Moss and Adams' heart disease in infants, children, and adolescents including the fetus and young adult - Allen, Hugh D.; Shaddy, Robert E.; Penny, Daniel J.; Cetta, Frank; Feltes, Timothy F. (Wolters Kluwer, 2016)
"The 9th edition of the gold standard in pediatric cardiology offers up-to-date, comprehensive coverage of this challenging and rapidly changing field. New chapters based on reader requests, two new associate editors, new contributing authors, and an enhanced digital version of the text make Moss and Adams' Heart Disease in Infants, Children, and Adolescents the reference you'll turn to when caring for patients. From cover to cover, this award-winning two-volume resource provides the authoritative, state-of-the-art information you need when caring for young patients with heart diseas"--Publisher's description.